1, 2, 4-Triazole derivatives as host materials for blue and green phosphorescent organic light-emitting devices. Issue 29 (21st July 2016) - Xu, Huixia; Sun, Peng; Wang, Kexiang; Miao, Yanqin; Yang, Tingting; Wang, Hua; Xu, Bingshe; Wong, Wai-Yeung
Abstract: A novel host material, namely 9-(6-(3-phenyl-5-(pyridin-2-yl)-4 H -1, 2, 4-triazol-4-yl)hexyl)-9 H -carbazole (PPHCZ) was designed and synthesized by incorporating 1, 2, 4-triazol as the electron-withdrawing moiety and carbazole as electron-donating moiety using hexyl as bridge. The photophysical, electrochemical, thermal properties and performances in phosphorescent organic light-emitting devices (PhOLED) were thoroughly characterized. PPHCZ with a high triplet energy level (3.01 eV) exhibited an obvious intermolecular interaction in thin film. Green and blue PhOLEDs using fac -tris(2-phenylpyridine)iridium and iridium(III) bis(4, 6-difluorophenyl)-pyridinato N, C 2 ′]picolinate as phosphorescent dopants have been fabricated. Graphical abstract: A novel host material, namely 9-(6-(3-phenyl-5-(pyridin-2-yl)-4 H -1, 2, 4-triazol-4-yl)hexyl)-9 H -carbazole (PPHCZ) was designed and synthesized. The material exhibited an obvious intermolecular interaction in solid state. The blue PhOLEDs using FIrpic as phosphorescent dopants was fabricated.